(Invited) SiGe and III-V Materials and Devices: New HEMT and LED Elements in 0.18-Micron CMOS Process and Design. (18th August 2016) - Fitzgerald, Eugene A; Lee, K.E.; Yoon, Soon-Fatt; Chua, S.J.; Tan, Chuan Seng; Ng, G.I.; Zhou, X.; Gong, Xiao; Chang, J.S.; Peh, L.S.; Boon, C.C.; Antoniadis, D.a.; et al.
Abstract : We have established new methodologies, materials, processing, devices, and circuits for integrating III-V devices monolithically into CMOS circuits. Certain constraints were applied on this research from the start in order to converge on viable commercial strategies as the research moves closer to a path for new innovation in the semiconductor industry. Integration technology has been established for incorporating HEMTs and LEDs into CMOS integrated circuits, and both nitride-based and arsenic-phosphide-based materials are currently supported. Device models are inserted into standard foundry design libraries, allowing silicon technology efficiencies such as exploring various circuit designs before final physical silicon and fabrication-test feedback loops using test chip designs.